Réponses

2012-12-05T20:10:41+01:00

(2x+3) [(2x+3) + (x+8)]

(2x+3) [2x+3+x+8]

(2x+3) [3x + 11]

(2x+3)(3x+11)

 

(2X(3/2)) (3X(3/2))

2012-12-05T20:11:08+01:00


1 développement :

E(x) = (2x -3)² - (2x - 3) (x + 8)

E(x) = 4x² - 6x -6 x + 9- (2 x² + 16x - 3 x² - 24)

E(x) = 4x² + 12 x + 9 + 2 x² - 16 x + 3 x² + 24

E(x) = 9 x² - 28 x + 33


2 Factorisation :

facteur commun (2x - 3)

E(x) = (2x - 3)² + (2 x -3) (x + 8)

E(x) = (2x - 3) (2 x - 3) + (2x - 3) (x + 8)

E(x) = (2x - 3) (2x - 3 + 2x - 3 + x + 8)

E(x) = (2x - 3) ( 5x + 2 )